Factors Behind Teachers’ Resistance to Participate in Professional Development in the Philippines: Basis in the Enhancement of Programs - Aquino, John Michael; Culajara, Carla Jobelle; Culajara, Juan Paolo Martin (Thai Journal of East Asian Studies, 2022)
Teachers, as the sole source of knowledge and skills, should have the grit to improve themselves through constant learning. The study adheres to identify the factors that hinder the participation of teachers in professional development. This study utilized a qualitative research design using a phenomenological approach. It was participated by five secondary public-school teachers with ten or above years in service working in the Philippines. The researchers used a purposive sampling in choosing the participants. Based on the result, three themes emerged: opportunities, teachers’ participation, and factors impeding professional development including financial literacy, time in continuing graduate studies, and teachers’ workload. Teachers have various opportunities to participate in their professional development however there are hampering factors that they need to consider. Along with the challenge of teachers to access to their professional growth and reach every student, the eagerness of teachers to deliver instruction and keep up with the trend is needed and achieved by each one. Thus, professional development must continue and make a path not only for students’ achievement but also for teachers’ satisfaction in their profession. This study will further enhance the crafting of a teacher’s enhancement program that focuses on the strengths and best practices of teachers. It will guide every teacher in Southeast Asian countries that they should value professional development because they are the ones who create the vision for ourselves and our students, thus, personal growth and professional development are successful, the foundation that they can provide to our students is also strong.